Reforming Business Registration in Greece : A Case Study - Conserva, Nicolas; Zanelli, Alessio; Muco, Sagita (World Bank, Washington, DC, 2021)
This case study explores the reforms of the business registration process implemented in Greece since 2005. It identifies lessons that can be valuable for public servants and policymakers in other countries, especially those who are considering reforming their business registration systems. The case study can also be useful to Greek policymakers and practitioners as they reform other areas of the business environment. In 2004, Greek entrepreneurs had to complete several procedures and go through a burdensome court-based process to register a business. Research suggests that streamlining business registration has the potential to support entrepreneurship, encourage the creation of new firms, and reduce informality, but of course needs to be considered in the backdrop of the broader business climate. From this perspective, establishing one-stop shops facilitates the registration of firms, which may be deterred by complex entry regulations.